TINJAUAN YURIDIS PERUBAHAN PENGATURAN JAMINAN HARI TUA BERDASARKAN PERATURAN MENTERI KETENAGAKERJAAN REPUBLIK INDONESIA NOMOR 19 TAHUN 2015 : Juridical Review Of Changes In Old-Age Pension Arrangements Based On Regulation Under Permenaker No. 19/2015 - Mohammad Farhan Fajari; Andari Yurikosari (Reformasi Hukum Trisakti, 2024)
The publication of Minister of Manpower Regulation Number 2 of 2022 was rejected by the public. Responding to this, on March 16 2022, the Minister of Manpower, Ida Fauziyah, explained that the rules for disbursement of Old Age Security (JHT) were in the process of being revised, so that disbursement (JHT) currently refers to Minister of Manpower Regulation Number 19 of 2015 (previous regulation). Permenaker 19/2015 after Permenaker 2/2022 was promulgated, the status is no longer valid and has been revoked with a new regulation (Permenaker 2/2022), so what is the legal status of Minister of Manpower Regulation Number 19 of 2015 if it refers to the regulatory foundations and guidelines in accordance with the Hierarchy Legislative Regulations, Are they in accordance with the Republic of Indonesia Government Regulation Number 12 of 2011 concerning the Formation of Legislative Regulations. The research method used is descriptive normative research based on primary and secondary data, which is analyzed qualitatively by drawing conclusions deductively.